Corneal clouding, cataract, and colobomas with a novel missense mutation in B4GALT7—a review of eye anomalies in the linkeropathy syndromes. Issue 10 (20th June 2016) - Arunrut, Teda; Sabbadini, Marta; Jain, Mahim; Machol, Keren; Scaglia, Fernando; Slavotinek, Anne
Abstract : We present a 5‐year‐old female with a distinctive phenotype comprising global developmental delays, pre‐ and post‐natal growth restriction, striking joint laxity with soft skin, and scoliosis. She had a triangular facies, a prominent forehead, proptosis, a small nose, and a small jaw. Her ocular findings included corneal clouding, colobomas of the iris and optic nerve, and posterior subcapsular cataracts. Exome sequencing identified homozygosity for c.970T>A, predicting p.(Cys324Ser), in the xylosylprotein 4‐beta‐galactosyltransferase, polypeptide 7 ( B4GALT7 ) gene. Variant segregation was consistent with autosomal recessive inheritance and the missense substitution was predicted to be pathogenic. As the phenotype of this child is consistent with that described in other "linkeropathy" syndromes, we conclude that p.(Cys324Ser) is likely to be disease‐causing. The eye features were a notable part of this child's presentation and mutations in the linkeropathy genes ( XYLT1, XYLT2, B4GALT7, B3GALT6, and B3GAT3 ) can be associated with ocular findings, including blue sclerae, refractive errors, corneal clouding, strabismus, nystagmus, cataracts, glaucoma, and retinal abnormalities, including retinal detachment. The corneal clouding and cataracts in this patient may thus have been caused by her B4GALT7 mutation, but the colobomas are a novel phenotypic finding. However, a different genetic etiology or a role for modifying genetic factors has not been excluded in the etiology of her colobomas. © 2016 Wiley Periodicals, Inc.